Regaining NATO's southern neighbours: The alliance should seize the opportunity to jointly reshape southern partnerships - Jane Kinninmont; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2024)
NATO's 2023 summit in Vilnius was dominated by Russia's war against Ukraine. The summit in Washington, D.C., in July 2024 will be influenced by an additional major conflict in NATO's neighbourhood: the war in Gaza and the related heightened tensions in the Middle East. These have also negatively impacted attitudes in the Middle East and North Africa (MENA) region towards many of the Alliance's members. The Vilnius summit decision to reflect deeply on NATO's southern neighbourhood turned out to be timely. An independent expert group appointed by NATO Secretary General Jens Stoltenberg contributed towards this reflection process. The group, which included the two authors of this paper, found there are shared security interests between NATO and countries in the south, including on counterterrorism and maritime security. Yet, security perceptions are far from identical, especially when it comes to the role of strategic competition. NATO needs to adapt its mindset to take advantage of opportunities for problem-solving cooperation with partners who may not share its views about international order, and who have concerns about the risk of importing a new Cold War.
Keywords: 320; NATO's 2023 summit in Vilnius; "360-degree approach" (NATO); Middle East and North Africa (MENA) region; NATO Secretary General Jens Stoltenberg; counterterrorism; maritime security; African Union; Arab League; Gulf Cooperation Council